2022
DOI: 10.1016/j.matpr.2021.12.123
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 prediction through X-ray images using transfer learning-based hybrid deep learning approach

Abstract: Over the past few months, the campaign against COVID-19 has developed into one of the world's most sought anti-toxin treatment scheme. It is fundamental to distinguish cases of COVID-19 precisely and quickly to help avoid this pandemic from taking a wrong turn with a proper medical reasoning and solution. While Reverse-Transcription Polymerase Chain Reaction (RT-PCR) has been useful in detection of corona virus, chest X-Ray techniques has proven to be more successful and beneficial at detection of the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“… CNN+ ELMs+ ChOA 2 99.11% 5 Thaseen et al (2022) ( 9 ) 13,808 X-ray images. Ensemble CNN model 3 99.00% 6 Kumar et al (2021) ( 10 ) 6000 X-ray images. HCNN 3 98.20% 7 Musallam et al (2022) ( 11 ) 7512 X-ray images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… CNN+ ELMs+ ChOA 2 99.11% 5 Thaseen et al (2022) ( 9 ) 13,808 X-ray images. Ensemble CNN model 3 99.00% 6 Kumar et al (2021) ( 10 ) 6000 X-ray images. HCNN 3 98.20% 7 Musallam et al (2022) ( 11 ) 7512 X-ray images.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the three-category accuracy of COVID-19, general pneumonia and normal was 99.00%. A hybrid convolutional neural network (HCNN) combining CNN and RNN on classification of three-category accuracy of COVID-19, general pneumonia and normal was proposed with the classification accuracy of 98.20% ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [ 30 ] proposed the hybrid convolutional neural network (HDCNN), which fuses convolutional neural network (CNN) and recurrent neural network (RNN) structure for detecting COVID-19 cases by utilizing chest x-ray images. With the increase in COVID-19 cases and X-rays, it is necessary to classify the x-ray with the help of transfer learning.…”
Section: Related Workmentioning
confidence: 99%
“… For efficient net Accuracy- 93.48% Precision value for COVID and normal class – 93% and 94% Recall value for COVID and normal class- 93% and 93% F1-score value for COVID and normal class- 93% and 94% Chen [ 6 ] CNN + HOG classifier A combination of 1 × 1 convolution blocks makes the structural design of CNN lighter with a minimum number of parameters. The overfitting issues is not handled properly by the drop-out layer • Accuracy- 92.95% • Recall- 85% • Specificity- 82% • Precision- 91.5% Demir [ 9 ] DeepCoroNet Deals with big datasets For real-world applications, it requires high memory bandwidth Kumar et al [ 30 ] Hybrid CNN By using HCNN, this system exhibits very promising outcome This model built over very minimum samples. • Accuracy- 98.20% • Precision- 97.31% • Recall- 97.1% • F1-score-0.97 Elaziz et al, [ 1 ] MobileNetV3 and Aquila optimizer algorithm Early diagnosis was performed efficiently It is unsuitable for agriculture, remote sensing, galaxy classification, and other image classification tasks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation